The Accuracy of Basal Area Increment with Increment Borer - Negi, G. S. (Indian Forester, 1967)
The paper presents the results of a study on the precision and accuracy of area increment by an increment borer and compares the area increment with that determined by a planimeter. 4 timber species were used in this study. The relative mean square errors were higher in magnitude than indicated by the estimates of precision while the area increments were underestimated in most cases.